V.l.n.r. : Van den Bergh, Gualthérie van Weezel, Scholten, Brinkhorst. Bij de bankjes: Ter Beek, Terlouw - Naeff, Nico,
V.l.n.r. : Van den Bergh, Gualthérie van Weezel, Scholten, Brinkhorst. Bij de bankjes: Ter Beek, Terlouw.